Fabrication of hydrogel mini-capsules as carrier systems [version 3; peer review: 1 approved, 4 approved with reservations] - Gaia Petrucci; Stefano Palagi; Elisa Roberti; Francesco Bianciardi (Open Research Europe, 2025)
Conventional drug administration often results in systemic action, thus needing high dosages and leading to potentially pronounced side effects. Targeted delivery, employing carriers like nanoparticles, aims to release drugs at a target site, but only a small fraction of nanoparticles reaches it. Microrobots could overcome this issue, being guided to hard-to-reach sites and locally delivering payloads. To enhance their functionality, we propose microrobots made as deformable capsules with hydrogel shells and aqueous cores, having the potential added advantages of biocompatibility, permeability, and stimulus-responsiveness. Endowing microrobots with deformability could allow them to navigate inside capillaries and cross barriers to finally reach the target site. In this study, we present a cost-effective method for fabricating core-shell structures without the use of organic solvents, surfactants, or extreme pH conditions. First, a mixture of hydrogels, agarose and alginate, is dripped into a calcium chloride solution to form beads. After they are loaded with calcium ions at different concentrations, they are immersed in an alginate solution to form the shell. Finally, the beads are heated to let the agarose melt and diffuse out, leaving a liquid core. By varying the concentration of calcium ions, we obtain shells of different thicknesses. We have correlated the measured shell thickness to its colour intensity and extrapolated to estimate the thickness of shells too thin to be measured directly. This allowed us to conclude that no continuous shells forms below a certain calcium chloride concentration. For higher concentrations, although the core may remain partially gelled, continuous shells successfully form. To qualitative assess core-shell capsule deformability, we forced them through a tube with an inner diameter ~1.6 times smaller than the average capsule diameter. The capsules deformed to pass through the constriction while maintaining structural integrity. Therefore, our fabrication method offers a promising platform for applications in drug delivery, encapsulation systems, and microrobotics.